2022
DOI: 10.3389/fmars.2022.844597
|View full text |Cite
|
Sign up to set email alerts
|

Selection Signatures of Pacific White Shrimp Litopenaeus vannamei Revealed by Whole-Genome Resequencing Analysis

Abstract: The Pacific white shrimp Litopenaeus vannamei is among the top aquatic species of commercial importance around the world. Over the last four decades, the breeding works of L. vannamei have been carried out intensively and have generated multiple strains with improved production and performance traits. However, signatures of domestication and artificial selection across the L. vannamei genome remain largely unexplored. In the present study, we conducted whole genomic resequencing of 180 Pacific white shrimps fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…This gene is detected under positive selection in a Scottish farmed population of Atlantic salmon (López et al, 2018). In addition, the gene scap (sterol regulatory element-binding protein cleavage-activating protein) was already identified under positive selection in six farmed Pacific white Shrimp populations (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This gene is detected under positive selection in a Scottish farmed population of Atlantic salmon (López et al, 2018). In addition, the gene scap (sterol regulatory element-binding protein cleavage-activating protein) was already identified under positive selection in six farmed Pacific white Shrimp populations (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of these genes in agronomic traits still needs explored. 13,146 As mentioned previously, the sex of an organism is an important economic trait because females and males generally exhibit different growth rates, particularly in shrimp, crayfish and crabs. 147,148 For example, Gammarus duebeni males tend to reach larger sizes than females.…”
Section: Genome-wide Association Studies Of Economic Traitsmentioning
confidence: 99%
“…13,115,[141][142][143][144][145] Genome resequencing and selection signature analysis has also confirmed that genes related to growth and disease resistance are indeed selected during the artificial breeding process. 13,146 After resequencing the genomes of wild and selectively bred broodstocks, a previous study elucidated that the nucleotide diversity of the genes encoding anti-lipopolysaccharide factor-like protein (ALF), A-kinase anchor protein 13 (AKAP13), and lactosylceramide 4-alpha-galactosyltransferase (A4GALT) were significantly lower in the selectively bred broodstocks. These findings demonstrated that these genes were selected during the artificial selection process and may be associated with growth and disease-resistance traits.…”
Section: Genome-wide Association Studies Of Economic Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…This great success of L. vannamei aquaculture is consequently due to favourable culture attributes and sustainable modern aquaculture technologies. These are included disease resistance and genetically improve specific pathogen free (SPF) brood stock, higher adaptability to culture conditions and eating various pelleted and live feeds and even small particles, as well as intensive and super-intensive modern culture systems like earthen/concrete ponds culture, recirculating aquaculture system, raceways and microbial/biofloc based systems (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%